Fault-based principle and no-fault rule: an analysis of Malaysian laws on employment injury compensation to migrant worker - Mohamad Amin, Noor Shuhadawati; Ali Mohamed, Ashgar Ali; Torla, Areej (LexisNexis Malaysia Sdn. Bhd., 2017)
The introduction of the no-fault rule in the employment injury compensation laws ousted the exclusive defences under common law that has long shielded the employers from becoming responsible for their employees' injury. Although the Employees' Social Security Act 1969 regulates the local workers has radically abolished the common law defences, leaving only the straightforward no-fault rule, the Workmen's Compensation Act 1952 on the other hand still maintains the civil law suits as an alternative for the migrant worker to claim for damages pursuant to the Civil Law Act 1956whichfounded on the fault-based principle. Hence, the focus of this article is to analyse the two concepts of claims available, the fault-based principle under common law and the recent no-fault rule. The article will also investigate the criticism of the fault-based principle and the no-fault rule within the ambit of the Malaysian employment injury compensation legislations. The main concern of this study are migrant workers therefore, the writers will review the migrant workers right to claim for compensation in the light of the employment injury compensation laws in Malaysia.